Productive Mis-mappings: Critical Disorientations on the University of South Carolina's Historic Horseshoe. (May 2017) - Cooley, Heidi Rae
Located at the heart of the University of South Carolina campus is the historic Horseshoe—originally the South Carolina College campus (est. 1801)—a site whose construction during the antebellum years relied on enslaved labor. Ghosts of the Horseshoe is a cross-College, collaborative "critical interactive" for iPad that features the Horseshoe campus and endeavors to make visible this unacknowledged history. The application uses as its dedicated navigational interface a historic 1884 Sanborn Fire Insurance map of the site; participants can also activate a Google Map overlay of the site and determine its degree of opacity with respect to the archival map image. Importantly, however, the two maps do not actually "map" onto each other. This serves as a first mis-mapping of several mis-mappings. This article considers how such mis-mappings, involving geo-locative contingencies, representational disjunctions, and potential dis-locations, mediate site-specific explorations and, as such, make possible alternative historiographic understandings of place.